Performance evaluation of MPEG-4 video transmission over IEEE802.11e - Mohammed Jama, Abdi Risaq; Issa, Sinzobakwira; Khalifa, Othman Omran (nternational Journal of Computer and Network Security(IJCSNS), 2010)
Transmitting MPEG-4 video over Wireless Local Area Networks is expected to be an important component of many emerging multimedia applications. One of the critical issues for multimedia applications is to ensure that the Quality of Service (QoS) requirement to be maintained at an acceptable level. The IEEE802.11 working group developed a standard called IEEE802.11e to support Quality of Service (QoS) in WLANs. This standard aims to support QoS by providing differentiated classes of service at the Medium Access Control (MAC) layer to enhance the ability of physical layers to deliver time-critical traffic in the presence of traditional data packets. In this Paper, Network Simulator 2 (NS-2) & Evalvid are used as simulation tool to evaluate the Performance of MPEG-4 Video Transmissions over IEEE802.11e. A modification of the parameters of NS-2 and Evalvid were done to present the evaluated method. This has allowed us to control the different design metrics values such as Frame/Packet loss, PSNR & Decodable Frame Rate (Q). In this paper, we evaluate a framework which consists of a MAC-centric cross-layer architecture to allow MAC layer to retrieve video streaming packet information, and a single-video multi-level queue to prioritize I/P/B slice (packet) delivery, the evaluated systematic scheme shows better results for lower packet loss, higher PSNR & Decodable Frame Rate (Q) for MPEG-4 video transmission over IEEE 802.11e..